2015
DOI: 10.1016/j.jevs.2015.03.154
|View full text |Cite
|
Sign up to set email alerts
|

142 Factors affecting basal and post-exercise prolactin secretion in horses

Abstract: concentrations were still on a linear trend upward at 96 h in all treated groups. Experiment 2 was similar to Exp. 1 and compared 1.5 versus 3 g of sulpiride injected in the thoracic area. Blood sampling was extended to 168 h. Prolactin patterns were the same as in Exp. 1, and concentrations were still elevated at 168 h (dose effect, P ¼ 0.11). The magnitude of the responses averaged 15 to 30 ng/mL at 96 h after injection in both experiments. These results indicate that Crisco shortening is as effective for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…are as yet largely untested/unvalidated in horses include oxytocin (urinary prolactin (which has been measured in horses and increases in response to exercise: Digiovanni et al, 2015; in response to stall confinement and transportation: King et al, 2009; and more recently in response to a surprise stimulus and social isolation: Bachman et al, 2017). McBride et al (2017) reviewed the use of spontaneous blink rate (SBR) as a marker of dopamine transmission in rodents, with increased dopamine associated with an elevated SBR.…”
Section: Physiological Components Warranting Further Investigation Inmentioning
confidence: 99%
“…are as yet largely untested/unvalidated in horses include oxytocin (urinary prolactin (which has been measured in horses and increases in response to exercise: Digiovanni et al, 2015; in response to stall confinement and transportation: King et al, 2009; and more recently in response to a surprise stimulus and social isolation: Bachman et al, 2017). McBride et al (2017) reviewed the use of spontaneous blink rate (SBR) as a marker of dopamine transmission in rodents, with increased dopamine associated with an elevated SBR.…”
Section: Physiological Components Warranting Further Investigation Inmentioning
confidence: 99%
“…In the spleen, the noradrenergic sympathetic fibers can take up circulating dopamine, which could then be released on sympathetic activation to be taken up in turn by leukocytes through active transport [ 47 ]. The finding of the current study showed an increase of prolactin levels after jumping competition that, hypothetically, could be due to an immediate antagonism of hypothalamic dopamine input to the pituitary, or to some other stimulation factors related to the hypothalamic–hypophysial portal system [ 18 , 48 ]. Thus, it could be assumed that the higher prolactin values recorded after competition are related to the superimposition of stimulatory input of prolactin-releasing factors, such as thyrotrophin-releasing hormone, arginine vasopressin, vasoactive intestinal peptide, and serotonin.…”
Section: Discussionmentioning
confidence: 99%